Evaluasi kesesuaian hasil manual assessment chart tool dan niosh lifting equation dalam mengidentifikasi keluhan muskuloskeletal dari aktifitas angkat beban manual pada pekerja di industri - Payzar Wahyudi; Widodo Hariyono (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
The agreement of manual assessment chart tool and NIOSH lifting equation in the identification of musculoskeletal complaints of industrial workersPurposeThis research aimed to compare the assessment results of two methods in assessing the risk of manual lifting activity and evaluating the conformity of the results in some industries.MethodsA cross-sectional study was conducted involving direct observation by image and video taking of 30 workers who performed manual lifting activities in three industrial sites. The data obtained were used to fill out the MAC tool sheets and NLE. ResultsThe results showed that the complaints in the back became the most common complaints felt by workers (56.7%). From the results of the assessment of manual lifting activity, we found 70% risk workers with MAC tool method and 76.7% with the NLE method. The suitability of the results of these two methods with the Kappa test was 0.83 which indicated the existence of a strong result match. ConclusionBoth MAC tools and NLEs had a strongly measured benchmark against the risk assessment of manual lifting activities, so that in their use they can replace each other.